Outgrowing the Immaturity Myth: The Cost of Defending From Neonatal Infectious Disease - Harbeson, Danny; Ben-Othman, Rym; Amenyogbe, Nelly; Kollmann, Tobias R. (Frontiers in Immunology, 2018)
Newborns suffer high rates of mortality due to infectious disease—this has been generally regarded to be the result of an “immature” immune system with a diminished disease-fighting capacity. However, the immaturity dogma fails to explain (i) greater pro-inflammatory responses than adults in vivo and (ii) the ability of neonates to survive a significantly higher blood pathogen burden than of adults. To reconcile the apparent contradiction of clinical susceptibility to disease and the host immune response findings when contrasting newborn to adult, it will be essential to capture the entirety of available host-defense strategies at the newborn’s disposal. Adults focus heavily on the disease resistance approach: pathogen reduction and elimination. Newborn hyperactive innate immunity, sensitivity to immunopathology, and the energetic requirements of growth and development (immune and energy costs), however, preclude them from having an adult-like resistance response. Instead, newborns also may avail themselves of disease tolerance (minimizing immunopathology without reducing pathogen load), as a disease tolerance approach provides a counterbalance to the dangers of a heightened innate immunity and has lower-associated immune costs. Further, disease tolerance allows for the establishment of a commensal bacterial community without mounting an unnecessarily dangerous immune resistance response. Since disease tolerance has its own associated costs (immune suppression leading to unchecked pathogen proliferation), it is the maintenance of homeostasis between disease tolerance and disease resistance that is critical to safe and effective defense against infections in early life. This paradigm is consistent with nearly all of the existing evidence.